Toxin and capsule production by Bacillus cereus biovar anthracis influence pathogenicity in macrophages and animal models. - Treenate Jiranantasak; Andrew P Bluhm; Donald J Chabot; Arthur Friedlander; Richard Bowen; Ian A McMillan; Ted L Hadfield; Airn Hartwig; Jason K Blackburn; Michael H Norris (PLoS Neglected Tropical Diseases)
Bacillus cereus biovar anthracis (Bcbva) causes anthrax-like disease in animals, particularly in the non-human primates and great apes of West and Central Africa. Genomic analyses revealed Bcbva as a member of the B. cereus species that carries two plasmids, pBCXO1 and pBCXO2, which have high sequence homology to the B. anthracis toxin and polyglutamate capsule encoding plasmids pXO1 and pXO2, respectively. To date, only a few studies have investigated the effect of variations in Bcbva sporulation, toxin, and capsule synthesis on animal and macrophage pathogenicity compared to B. anthracis, therefore more research is needed to gain a better understanding of the pathogenesis of this emerging infection. Here, we report that Bcbva can multiply and vegetatively survive on nutrient-rich media for a minimum of six days while generating spores. Sporulation of Bcbva occurred faster and more extensively than B. anthracis Ames. Bcbva tended to secrete less protective antigen (PA) than B. anthracis Ames when cultured in growth medium. We found Bcbva produced a substantially higher amount of attached poly-ƴ-D-glutamic acid (PDGA) capsule than B. anthracis Ames when grown in medium supplemented with human serum and CO2. In a phagocytosis assay, Bcbva spores showed reduced internalization by mouse macrophages compared to B. anthracis Ames. Our research demonstrated that Bcbva is more virulent than B. anthracis Ames using two in vivo models, Galleria mellonella larvae and guinea pigs. Following that, the efficacy of the veterinary vaccine Sterne strain 34F2 against anthrax-like disease was assessed in guinea pigs. Sterne vaccinated guinea pigs had significantly increased anti-PA titers compared to the unvaccinated control group. Toxin neutralizing antibody titers in vaccinated guinea pigs correlated with anti-PA titers. This indicates the Sterne vaccine provides adequate protection against Bcbva infection in laboratory animals.